Oyster production and meat yield in Crassostrea spp. (bivalvia: Ostreidae) in Pinar del Rio, Cuba - Mazón-Suástegui, José Manuel; Betanzos-Vega, Abel; Capetillo-Piñar, Norberto; Latisnere-Barragán, Hever; Ortiz-Cornejo, Nadia Livia (Ecosistemas y Recursos Agropecuarios, 2018)
The main fishing enterprise located in the province of Pinar del Río, Cuba, markets oyster meat packed in brine bags of 460 g. Oysters come from natural bank fisheries and farms. During the period 2009 – 2013, captures showed an increasing tendency from 50 t to more than 80 t.However, the recorded oyster meat yields values from 3.3 – 3.9% are considered lower than the minimal acceptable value (4.9%). The aims of this study were to assess oyster exploitation, meat yield and loss in the final packed product. Monthly and annual variations of meat yield were analyzed regarding capture and oyster size; meanwhile, the meat loss was analyzed by treatments with different proportions of oyster / brine. Significant difference (p< 0.05) of meat yield (%) was observed by oyster species and size with a better performance in farmed oysters. Traditional packing for commercialization (meat / brine, 391 g / 69 g, respectively, and total weight of 460 g) influenced meat weight loss by leakage of interstitial fluid; this loss was further confirmed by the treatments with different proportions of meat / brine where the 1:1 proportion showed the least meat weight loss. In addition, the non-compliance of management measures regarding commercial size, as well as lack of oyster cleanliness before shell removing process, impacted meat yield analyses during 2009-2013.